Industrial Wastewater Treatment in North Gas Company By Using Coagulation – Flocculation Process - Kamal, Sanarya K.; Mohammed, Awad E.; Alabdraba, Waleed M.; Hamed, Hussein H.; Waly, Kamaran A. (Journal of Petroleum Research and Studies, 2020)
Recently, water pollution considered a major problem that faced the human. Large quantities of water consume in various industrial oil refinery processes, where the wastewater discharged from these processes contains high organic, phosphate, ammonia, nitrite compounds, and toxic substances. Regarding that, making this resource a fresh is a major concern. Furthermore, a great attention has been given for the removal of these contaminants discharged by Fenton process combined with coagulation process. Combined Fenton/Coagulation process was used and applied in this study as a novel wastewater treatment to remove Chemical Oxygen Demand (COD), Phosphate (PO4), Ammonia (NH3), Nitrite (NO3) compounds, and turbidity (NTU) from industrial wastewater in North Gas Company (NGC), Iraq. The industrial wastewater used in this study was characterized with 114 mg/L COD ,10.28 mg/L PO4, 4.123 mg/L NH3, 95.6 mg/L NO3, 98 NTU Turbidity. The main goal from this work was to evaluate the performance removal efficiency of combined Fenton/Coagulation process and examine the effect of various operational parameters such as Fenton’s dosages (H2O2, Fe2+), the concentration of coagulant (Alum) on the removal efficiency. The results obtained in this work revealed that maximum removal efficiency of COD, PO4, NH3, NO3, turbidity was 89.43%, 72.94 %, 91.065%, 90.96%, 89.85%, respectively was achieved using Fenton combined with coagulation process at 60 mg/L of Alum and 2.5 Fenton’s mole ratio. Overall it can be established that Combined Fenton/Coagulation process plays an important role in obtaining good results and had better removal efficiency. All the experiments were carried out using jar test apparatus at constant temperature (room temperature).